The role of gender as moderator between cognitive - emotional regulation strategies and internalizing / externalizing behavioral problems among adolescents - Momtaz, Vahid; Mansor, Mariani; Abu Talib, Mansor; Kahar, Rojanah (UAD Press, 2016)
Internalizing/externalizing behavioural problems among adolescents are the most important issue in adolescents’ mental health. Cognitive-emotional regulation strategies are the important protective and risk factor for internalizing/externalizing behavioural problems. In the present study the moderating role of gender in the relationship between cognitive-emotional regulation strategies and internalizing/externalizing behavioural problems among adolescents was investigated. The respondents were 328 students who filled out Youth Self Report and Cognitive-Emotional Regulation Questionnaire. The moderating effect of gender were estimated by AMOS and the model fit indicated that gender did not have any significant moderating role in the relationship between positive and negative cognitive-emotional regulation strategies and internalizing/externalizing behavioural problems among adolescents.